Comparisons for determinants of special matrices by algorithm proposed - Zake, Lugen M.; Ibrahim, Haslinda; Omar, Zurni (World Academic Press, World Academic Union, 2011)
This paper presents the results of an early which compared the new algorithm to special matrices, purpose to calculate the value of determinant. Matrices which are numerically reliable techniques are used for this purpose. This technique permits for accuracy in the sense that it breaks down the new determinant for comparison to improve the existing numerical algorithms and to calculate the determinant of matrix.